Innowacje narzędziem przedsiębiorczości - Piecuch, Teresa (Innovation as a Tool of Entrepreneurship, 2006)
The aim of the article is to show the role of innovations and entrepreneurship in a market economy. Special attention was turned to the innovation level in Polish enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 128-135